Epigenetic regulation of insulin-like growth factor binding protein-3 (IGFBP-3) in cancer - Perks, Claire M (J Cell Commun Signal, 2015)
Epigenetics refers to heritable changes in gene expression that are independent of alterations in DNA sequence. It is now accepted that disruption of epigenetic mechanisms plays a key role in the pathogenesis of cancer: culminating in altered gene function and malignant cellular transformation. DNA methylation and histone modifications are the most widely studied changes but non-coding RNAs such as miRNAs are also considered part of the epigenetic machinery. The insulin-like growth factor (IGF) axis is composed of two ligands, IGF-I and –II, their receptors and six high affinity IGF binding proteins (IGFBPs). The IGF axis plays a key role in cancer development and progression. As IGFBP genes have consistently been identified among the most common to be aberrantly altered in tumours, this review will focus on epigenetic regulation of IGFBP-3 in cancer for which the majority of evidence has been obtained.